Solubility enhancement study of lumefantrine by formulation of liquisolid compact using mesoporous silica as a novel adsorbent - Sayani Bhattacharyya; Daivanai Ramachandran (Materials Letters: X, 2022)
Lumefantrine, exhibits poor bioavailability due to its very low solubility. A liquisolid compact of lumefantrine was prepared with mesoporous silica as a novel coating material. Lactose anhydrous and syloid 244FP were selected as carrier and coating materials respectively. Varying the carrier to coating ratio from 10 to 35, six formulations were prepared and evaluated for tests for tablets. thermal, surface characteristics, surface morphology, and surface area analysis. The tabletability of the formulation lactose to syloid 244FP ratio at 20:1 was found to be the best among all in terms of compression characteristics, faster disintegration, and enhanced dissolution. Hence it can be concluded that the use of a suitable amount of mesoporous silica in the formulation of liquisolid compact could significantly enhance the dissolution of the drug.